Development and assessment of a decentralized management system for doctoral student administration - Alexandr Bazhin; Mara Taverna; Serene Lee; Barbara Mayer; Jens Werner (Har Press Indonesia, 2021)
The main aim of this project was to establish a decentralized management and administration system for doctorates at the research unit of the Department of General, Visceral, and Transplant Surgery at the Medical Faculty of Ludwig-Maximilians-University Munich. A flow process chart conforming to the quality management system and detailing the sequence of a standardized initial introduction has been established. In order to determine if the introduction in each core facility was successful, a multiple-choice evaluation was implemented. Secondly, a welcome package has been created, which contains important information on how to start work in the department and also describes the necessary introductions and briefings and their sequence. Between 2018 and 2020, 20 applicants were accepted as doctoral students in the Department, two of them already finished their experimental work. Median duration of the introductory procedure was 20 days with minimum of six (6) and maximum of 121 days. Analysis of the test results revealed that in four types of briefings, all students passed the tests on the first attempt. However, for four other types of introductions, 5-31% of the students had to repeat the introductions due to failing the aptitude tests. All students were subsequently able to pass the aptitude tests at least on their second attempt. We successfully developed a decentralized management and administration system for doctorate students. Based on internal evaluations using key-indicators as well as the SWOT analysis, we can conclude that this management system could be used by research facilities that educate doctorate students.